CONSTRUCTION OF ABORTION CRIMINAL PROVISIONS IN THE REFORM OF THE NATIONAL CRIMINAL CODE - Munandar, M. Aris (Sekolah Tinggi Ilmu Hukum Awang Long, 2023)
The construction of criminal sanctions for perpetrators of the crime of abortion in Law of the Republic of Indonesia Number 1 Year 2023 concerning the Indonesian Criminal Code (Kitab Undang-Undang Hukum Pidana/KUHP) in general contains a change in perspective regarding abortion. The criminalization of abortion in the National Criminal Code is a form of reform in law enforcement for the crime of abortion. The method of research used in normative legal research. The result of research reduction in the threat of imprisonment in the National Criminal Code for abortion perpetrators indicates a moderation of criminal sanctions for perpetrators of criminal acts. This is very different from the spirit of the Law of the Republic of Indonesia Number 36 Year 2009 concerning health (the Health Law) in preventing abortion. This is because abortion is indeed a field of criminal health law, which expresses the verb is and should indeed be regulated in health law as a lex specialist. However, there are also efforts to benefit that are proposed in the National Criminal Code, namely by providing 14 (fourteen) weeks of pregnancy termination for women who wish to have an abortion either for medical indications or for the crime of rape or other criminal acts of sexual violence.